2015
DOI: 10.3892/ijo.2015.3103
|View full text |Cite
|
Sign up to set email alerts
|

Atg5 siRNA inhibits autophagy and enhances norcantharidin-induced apoptosis in hepatocellular carcinoma

Abstract: Abstract. Cantharidin is a terpenoid isolated from Chinese blister beetles, and norcantharidin (NCTD) is a demethylated analog of cantharidin. It has been reported that cantharidin and norcantharidin have anticancer activities. Growing evidence suggests that inhibiting autophagy can induce apoptosis in the human hepatoma cell line HepG2. The objective of the present study was to determine whether inhibition of autophagy enhances NCTD-induced apoptosis in HepG2 cells. HepG2 cells were cultured in DMEM containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…Consistent with this finding, the levels of cleaved caspase‐3 and PARP were higher following FHL1 silencing, further indicating that autophagy was inhibited and contributes to myofiber degeneration and weakness. Similar results were reported by Xiong et al () in which Atg5 silencing increased the expression of cleaved caspase‐3, caspase‐9, and PARP, leading to the inhibition of autophagy and enhanced apoptosis in hepatocellular carcinoma cells. Autophagy is a complex regulatory process.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with this finding, the levels of cleaved caspase‐3 and PARP were higher following FHL1 silencing, further indicating that autophagy was inhibited and contributes to myofiber degeneration and weakness. Similar results were reported by Xiong et al () in which Atg5 silencing increased the expression of cleaved caspase‐3, caspase‐9, and PARP, leading to the inhibition of autophagy and enhanced apoptosis in hepatocellular carcinoma cells. Autophagy is a complex regulatory process.…”
Section: Discussionsupporting
confidence: 89%
“…The inhibition of autophagy in HepG2 cells has pro-apoptotic effects, partly through enhanced ROS generation and activation of the mitochondrial apoptotic pathway, although the exact function of autophagy in apoptosis remains to be studied further [87]. Recent reports revealed that oxidative stress-triggered autophagic cell death is independent of apoptosis [87], suggesting that the processes of apoptosis and pro-survival autophagy are interrelated in a complicated manner or occur independently of each other. Therefore, the interplay between autophagy and apoptosis is controversial, and the scenario of autophagy in deciding cell destiny is elusive.…”
Section: Ca2+ Connection In Autophagy and Apoptosismentioning
confidence: 99%
“…It has been reported that Cantharidin (CTD), an active chemical compound isolated from the blister beetle (Coleoptera: Meloidae), serves a notable role in promoting autophagy and suppressing hepatocellular carcinoma (13). Consequently, one aim of the present study was to investigate the association between CTD and autophagy.…”
Section: Introductionmentioning
confidence: 99%